COMPARATIVE ANALYSIS OF HEPATOPROTECTIVE PROPERTIES OF GLIFLOZINS IN PATIENTS WITH TYPE 2 DIABETES AND NONALCOHOLIC STEATOHEPATITIS - Protas, Nadiia; Kostitska, Iryna; Protas, Yurii; Lehun, Myroslav (Eastern Ukrainian Medical Journal, 2025)
Introduction. Type 2 diabetes (T2D) and non-alcoholic steatohepatitis (NASH) are considered by world experts to be global non-communicable epidemics. Undoubtedly, the main aim of the medical community is to develop patient-centred principles for the treatment of people with comorbidities. The aim of the study was to evaluate the hepatoprotective properties of glyflozins.Methods. We examined 54 patients with T2D and NASH, who were divided into three study groups: Group I (n=18) received basic medical therapy (BMT): metformin – 2000 mg/day, alpha-lipoic acid – 600 mg/day, rosuvastatin – 10 mg/day; group II (n=18) used BMT in combination with dapagliflozin at a daily dose of 10 mg and group III (n=18) received 10–25 mg/day of empagliflozin. The study period lasted 12 weeks.Results. After 12 weeks of treatment with dapagliflozin/ empagliflozin as part of BMT promotes more than a twofold reduction in the biomarker of liver fibrosis (II, III groups: FIB-4: ∆‑34.50%, ∆‑35.10%, p<0.001, respectively), while in patients of I group this index decreased by 22.44%. A significant reduction in the liver fibrosis (HEPAmet) was confirmed in patients of II groups (∆‑81.09%, p<0.001) and III (∆‑76.62%, p<0.01). The findings of shear wave elastography of the liver indicate that in patients of II group a significant decrease in liver parenchymal stiffness by 10.73% (p<0.001), in group III – by 13.97% (p<0.001), while in patients of group I a positive trend was found without statistically significant changes (∆‑3.39%, p>0.05).Conclusions. Glyflozins demonstrate an alternative hepatocentric approach to achieving compensation of carbohydrate and lipid metabolism. After 12 weeks of BMT in combination with dapagliflozin/empagliflozin contributes to a significant reduction in markers of liver fibrosis with a tendency to reduce liver stiffness according to the METAVIR scale.